2004
DOI: 10.1177/00238309040470030401
|View full text |Cite
|
Sign up to set email alerts
|

Speech Rate in a Pluricentric Language: A Comparison Between Dutch in Belgium and the Netherlands

Abstract: This paper investigates speech rate in two standard national varieties of Dutch on the basis of 160 15 mins conversations with native speakers who belong to four different regions in the Netherlands and four in the Dutch-speaking part of Belgium (Flanders). Speech rate was quantified as articulation rate and speaking rate, both expressed as the number of syllables per second (syll/s). The results show a significant effect of speakers' country of origin: subjects in the Netherlands speak 16% faster than subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
95
2
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 17 publications
14
95
2
15
Order By: Relevance
“…In terms of voice quality, an extremely tense laryngeal setting was noted which caused the voice to sound generally metallic. As far as prosody is concerned, speech rate was normal (3.89 syllables/second) as compared to benchmark figures for Dutch in Verhoeven et al (2004). Speech rate was quantified as articulation rate, i.e.…”
Section: Patient Tlmentioning
confidence: 99%
“…In terms of voice quality, an extremely tense laryngeal setting was noted which caused the voice to sound generally metallic. As far as prosody is concerned, speech rate was normal (3.89 syllables/second) as compared to benchmark figures for Dutch in Verhoeven et al (2004). Speech rate was quantified as articulation rate, i.e.…”
Section: Patient Tlmentioning
confidence: 99%
“…This is due to the differences in syllable and word structure between languages and even between dialects of the same language [12]. For example, native speakers of British English were reported to exhibit a speaking rate of 3.16-5.33 SPS, whereas French speakers used a rate of 4.31-5.73, Portuguese 6.57 and Spanish 7.81 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bruckl and Sendlmeier [33], for example, have reported no effect of age on speaking rate in adults. Others, however, have suggested that older speakers exhibit a slower speaking rate [13]. Additionally, listeners were shown to perceive speakers who use slower speaking rate as older than those who use a faster speaking rate [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that the speakers' age and gender have an influence on AR: young speakers articulate faster than older speakers, and males articulate faster than females (Jacewicz, Fox, O'Neill & Salmons, 2009;Quené, 2008;Schwab & Racine, 2012;Smith, Wasowicz & Preston, 1987;Verhoeven, De Pauw & Kloots, 2004). AR also varies as a function of the speaking style.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, AR may depend on the speaker's regional variant (e.g. Jacewicz, Fox & Wei, 2010, for American English; Verhoeven et al, 2004 andQuené, 2008, for Dutch). As far as variants of French are concerned, AR is still an issue under debate.…”
Section: Introductionmentioning
confidence: 99%